Determinants of Budget Managers' Performance at Mpu Kuturan Singaraja State Hindu College: An Analysis of Budget Participation, Goal Clarity, and Organizational Commitment - Putu Wika Putrawan; Edy Sujana; I Gusti Ayu Purnamawati (Jurnal Ilmiah Akuntansi, 2024)
In the fiscal year 2022, the Mpu Kuturan Singaraja State Hindu College, as a work unit under the Ministry of Religion, was unable to achieve the budget absorption targets stated in the performance agreement. Consequently, it is necessary to identify the factors affecting the performance of budget managers. These factors include budget participation, clarity of budget goals, and organizational commitment. This study is descriptive research with a quantitative approach, utilizing both primary and secondary data. The results reveal that budget participation has a negative and significant effect on the performance of budget managers. Conversely, the clarity of budget goals and organizational commitment variables positively and significantly affect budget managers' performance. Furthermore, this study examines indirect influences, showing that budget participation mediated by organizational commitment negatively and significantly impacts budget managers' performance. In contrast, clarity of budget goals mediated by organizational commitment positively and significantly affects budget managers' performance. These findings highlight the importance of clear budget goals and strong organizational commitment in enhancing the performance of budget managers, while budget participation alone may not be sufficient. This research provides valuable insights for improving budget management practices at educational institutions and similar organizations, emphasizing the need for strategic alignment and commitment to achieve budgetary targets.